1997
DOI: 10.1093/humrep/12.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ovarian volume by transvaginal sonography before ovulation induction with human menopausal gonadotrophin for in-vitro fertilization can predict poor response

Abstract: The study tests the hypothesis that small ovaries measured on transvaginal sonography (TVS) are associated with a poor response to ovulation induction by human menopausal gonadotrophin (HMG) for in-vitro fertilization (IVF). A total of 140 infertile patients with morphologically normal ovaries undergoing IVF was studied. The mean ovarian volume of each patient was measured on TVS before starting HMG. Subsequent routine IVF management was conducted without knowledge of the results of TVS. The mean ovarian volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
0
19

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(123 citation statements)
references
References 19 publications
7
97
0
19
Order By: Relevance
“…The results of the current study, as well as those reported by others, do support that ovarian volume, measured by transvaginal ultrasound, has been correlated well with response to ovulation induction in ART cycles (18)(19)(20)32). Small ovaries (<3 cm 3 ) were found to predict poor response to ovarian stimulation and high cancellation rates but not pregnancy achievement (19). It was also reported that a significant decrease in the number of follicles and a higher cancellation rate observed in women with ovarian volume smaller than 3 cm 3 (18).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study, as well as those reported by others, do support that ovarian volume, measured by transvaginal ultrasound, has been correlated well with response to ovulation induction in ART cycles (18)(19)(20)32). Small ovaries (<3 cm 3 ) were found to predict poor response to ovarian stimulation and high cancellation rates but not pregnancy achievement (19). It was also reported that a significant decrease in the number of follicles and a higher cancellation rate observed in women with ovarian volume smaller than 3 cm 3 (18).…”
Section: Discussionsupporting
confidence: 91%
“…Our cut-off point for ovarian volume that discriminated the poor and normal responder was 2.98 cm 3 with a sensitivity of 75% and specificity of 81.2%. The results of the current study, as well as those reported by others, do support that ovarian volume, measured by transvaginal ultrasound, has been correlated well with response to ovulation induction in ART cycles (18)(19)(20)32). Small ovaries (<3 cm 3 ) were found to predict poor response to ovarian stimulation and high cancellation rates but not pregnancy achievement (19).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Along with an age-related decrease in estrogen levels, the absence of the beneficial effects of estrogen on oxidative stress finally causes damage to the ovaries. This may explain the significantly increase in the rate of congenital birth defects in women over age 38 (17). The accumulation of oxidative damage and an accompanying diminishing of antioxidant defenses will ultimately lead to ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…Possible markers include female age, early follicular serum FSH (18), estradiol and inhibin B concentrations (19), and ultrasonographic parameters including ovarian volume (20), antral follicle count (21), and peak ovarian stromal blood flow velocity (7). Further work is required on selecting stimulation protocols and appropriate starting doses of gonadotropins for women identified to be at increased risk of poor ovarian response.…”
Section: Discussionmentioning
confidence: 99%